Layanan Mobile Banking Di Indonesia: Tinjauan Persepsi Dan Harapan Pengguna Di BCA, BNI Dan BRI Menggunakan Teori Sinyal - Farizah Farhana; Salwa Amalia Balqis; Safinatun Naja; Anita Wulansari (Lembaga Pengembangan Kinerja Dosen, 2023)
In the era of technological advances and financial deregulation policies, competition between banks is getting tougher. M-Banking is a provider of various facilities to make it easier for customers to carry out online transactions. Nonetheless, some concerns still exist regarding the security and feasibility of the features provided by each bank. In this study, Signaling Theory is used to explore the level of customer satisfaction in utilizing m-banking services. The purpose of this study is to compare the feasibility of features, ease of access, and security of Mobile Banking transactions at three leading banks in Indonesia, namely BNI, BCA and BRI, from the point of view of customer preference. This research will use quantitative methods by collecting data through a survey using a questionnaire. It is hoped that the results of this study can provide a picture of preferences for customers in each bank, so that it can be taken into consideration in improving work systems and services to customers compared to other banks. The variables to be examined are the characteristics of each bank such as service, feasibility of features, interface design, and convenience for customers to access M-Banking.